Discontinuous Galerkin Methods on hp-Anisotropic Meshes I: A Priori Error Analysis - Georgoulis, Emmanuil H.; Hall, Edward; Houston, Paul (2006)
We consider the a priori error analysis of hp-version interior penalty discontinuous Galerkin methods for second-order partial differential equations with nonnegative characteristic form under weak assumptions on the mesh design and the local finite element spaces employed. In particular, we prove a priori hp-error bounds for linear target functionals of the solution, on (possibly) anisotropic computational meshes with anisotropic tensor-product polynomial basis functions. The theoretical results are illustrated by a numerical experiment.